Sex differences in lower limb neuromuscular function and asymmetry among 14–15 years old elite basketball players - Lyu, Mengde; Pappas, Evangelos; Ding, Ling; Qian, Huaibin; Huang, Jinglei; Farragher, Joshua; Ganderton, Charlotte; Xenos, Sophia; Lyu, Jie; Han, Jia (Frontiers in Physiology, 2025)
ObjectivesThis study aimed to compare inter-limb asymmetry in balance, jumping and strength between male and female basketball players aged 14–15 years old.DesignCross-sectional observational study.MethodsSixteen male and 16 female youth elite basketball players performed the Y-Balance, two jump tests; the single-leg countermovement and broad jumps and isokinetic knee strength tests. The inter-limb asymmetry index was calculated.ResultsThe inter-limb difference in the Y-balance test and the single leg jumps was 5%–10%, while the difference in knee flexion and extension strength were 10%–35%. In terms of sex differences, the Y-balance asymmetry in males was significantly higher than that in females (males: 8.57% ± 4.01% vs. females: 4.04% ± 3.14%, p = 0.001), with no differences in any of the other outcomes. In terms of performance, female players performed significantly worse than their male counterparts in both types of single leg jumps and strength (p ≤ 0.01), except right knee extension (p = 0.07).ConclusionIn 14–15 years old basketball players, large side-to-side asymmetries exceeding 20% were observed, however, there were largely similar in males and females, suggesting that the higher risk of lower extremity injury in females may not be due to asymmetry. Although no lower limb injuries were present in these participants, inter-limb strength differences were nearly 20%, highlighting the need for specific inter-limb difference training. Longitudinal studies are warranted to explore whether this asymmetry is associated with a higher risk of injury in this group of basketball players.